THYMOQUINONE AND ALBENDAZOLE AS UNCOMPETATIVE INHIBITORS OF GLUTATHIONE-S-TRANSFERASE IN Moniezia expansa: IMPLICATIONS FOR ANTHELMINTHIC THERAPY (Applied Biological Research, 2024)
The infection of Moniezia expansa is common among sheep and goat in the Indian sub-continent, and little is known about their detoxification ability. Therefore, in this study specific activity of glutathione-S-transferase (GST), along with its kinetic parameters like Km, Vmax, pH and temperature optima were investigated before and after treatment of worms with thymoquinone (TQ), and albendazole (ALBZ). Worms were collected from the infected small intestine of goats (Capra hircus) washed in Hanks' medium and incubated separately in RPMI 1640 medium with and without 120 µM TQ and ALBZ at 37ºC for 4 h. The specific activity of GST in the somatic extract of M. expansa was found to be 59.12 µ mole min-1 mg-1 protein. The optimum temperature and pH were found to be 25˚C and 6.5, respectively. It was observed that the rate of reaction increased with the increasing concentration of both GSH and CDNB; and maximum velocity (Vmax) of enzyme was recorded at 2 mM concentration for both the substrates. The Km value was higher while Vmax was lower in both TQ and ALBZ treated worms than control, indicating that both TQ and the ALBZ act as uncompetitive inhibitors of GST in M. expansa and appeared to be equally effective in inhibiting the GST activity, possibly through conformational changes of enzyme. This type of inhibition may greatly affect the detoxification ability of the worms and, therefore, their survival in the host; hence, GST of M. expansa could be exploited for therapeutic intervention and thymoquinone could be further tested at the in vivo level for dose standardization and field application.
Keywords: Albendazole; glutathione-S-transferase; Moniezia expansa; cestode; thymoquinone